(untitled) (International Journal of Nursing Education, 2023)
Introduction: Exercise is a bodily activity that improves or maintains physical fitness and overall health and wellness exercise during pregnancy is important and can help with some common discomforts of pregnancy and even help prepare the pregnant women body for labor and delivery. (6) Objective: To study the pregnant women knowledge regarding exercise during pregnancy. Methods This is a descriptive cross sectional hospital base study which was carried out in military hospital in Khartoum state - Sudan, the data were collected by structured questionnaire and analyzed using the statistical program for social sciences (SPSS) version 21Convenient sampling technique was used and the samples were 70 pregnant women. The knowledge is categorized good (>60%), Moderate (50%-60%), poor (< 50%). A statistical significance was considered at p-value of < 0.05. Result: The study revealed that the total mean knowledge about type of exercise was (95.7%), walking was the most common exercise among the study sample, 90.0 believe that exercise during pregnancy facilitates normal delivery, and vaginal bleeding was considered as contraindication among (84.3%). factors influencing exercise during pregnancy (31.4%) said fear from complication is one of the factors influencing exercise during pregnancy The overall knowledge of pregnant women about exercise during pregnancy was poor (36.3%:). Conclusion: Nursing education is the major tasks of nursing profession. The study concluded that there is insufficient knowledge of pregnant women about exercise during pregnancy 52 (74.3%). Fallowed by no relation between educational level, age and knowledge about type of exercise, regarding benefits and contraindications to exercise during pregnancy (p. value < 0.05). so the study recommended to conduct more researches to enhance in increasing mother’s knowledge about exercise during pregnancy.